Analisis Harga Pokok Penjualan pada Model Bisnis Thrift Shop Celana Bekas Berbasis Live Streaming Facebook: Studi Kasus pada Platform E-Commerce @sinsin (Jurnal Riset Manajemen dan Akuntansi, 2025)
The secondhand pants thrift shop industry based on Facebook live streaming has experienced significant growth in line with the increasing consumer interest in preloved products and the convenience of digital technology. This study aims to analyze the determination of the Cost of Goods Sold (COGS) in the @sinsin thrift shop business, an online store specializing in selling secondhand pants through Facebook's live streaming feature. The research method used is a descriptive qualitative approach, with data collection techniques including in-depth interviews with the business owner, direct observation of live streaming sessions, and documentation of sales and purchase records. The results of the study show that the calculation of COGS at @sinsin thrift shop is based on direct variable cost components such as the purchase price of pants, laundry costs, packaging, and shipping. Meanwhile, digital operational costs such as internet data, streaming equipment, and advertising are not directly included in the COGS but are proportionally allocated per product unit to obtain a more accurate estimate of total costs. Live streaming has proven effective in increasing customer trust, expanding market reach. The conclusion of this study indicates that using the full costing method allows business owners to adjust selling prices.